The Elements of a Successful Crowdfunding Campaign: A Systematic Literature Review of Crowdfunding Performance - Kaartemo, Valtteri (Senate Hall, 2017)
Crowdfunding campaigns are widely designed based on intuition rather than strategy. This systematic review gathers scattered knowledge on the elements that influence crowdfunding performance. The review provides guidance for practitioners on how to run a successful crowdfunding campaign, and it suggests topics and themes to advance the field further. The review identifies four main categories that affect crowdfunding performance: (1) campaign-, (2) crowdfunder-, (3) crowdfunding platform-, and (4) fund-seeker-related factors. Empirical research findings within these categories are synthesized and evaluated. It was found that there are still substantial gaps in our knowledge of crowdfunding performance, which opens avenues for future research. In addition, the review reveals methodological shortcomings in the field and calls for further research on the topic in general. In particular, many intuitive suggestions made by crowdfunding platforms need to be subjected to rigorous academic research. Keywords: crowdfunding, campaign, performance, literature review, crowdfunder, platform, fund-seeker
Keywords: crowdfunding|campaign|performance|literature review|crowdfunder|platform|fundseeker